Wideband Acoustic Absorbance in Otosclerosis: Does Stapedotomy Restore Normal Tympanic Cavity Function?* - Durante, Alessandra Spada; Nascimento, Polyana Cristiane; Almeida, Katia de; Servilha, Thamyris Rosati; Marçal, Gil Junqueira; Neto, Osmar Mesquita de Sousa (International Archives of Otorhinolaryngology, 2022)
Introduction Otosclerosis is characterized by the fixation of the stapes to the oval window, thereby impairing acoustic signal absorbance. A commonly used surgical technique for improving hearing in cases of otosclerosis is stapedotomy. However, it is unclear whether this surgery restores all the physical characteristics of the tympano-ossicular system.Objective To evaluate the tympano-ossicular system in individuals with fenestral otosclerosis pre and poststapedotomy using wideband tympanometry.Method A total of 47 individuals and 71 ears were assessed. The subjects were divided into three groups: presurgery otosclerosis; postsurgery; and a control group of normal-hearing adults. A handheld tympanometer with a wideband module (226–8,000 Hz) was used to take measurements at ambient pressure and under pressurized conditions. The level of statistical significance adopted was p ≤ 0.05.Results Acoustic absorbance at 226 Hz was low for all groups. At frequencies in the range 630 to 5,040 Hz, each group had a characteristic absorbance curve, allowing them to be distinguished from one another. In the presurgery group, absorbance values were below normal levels, with energy absorbance below 10%. Low energy absorbance was most evident at 1,000 Hz in the presurgery group, but this was not observed in the postsurgery group. Although there was an improvement in hearing, the surgery failed to restore the tympano-ossicular system to normal.Conclusion Wideband acoustic absorbance proved able to differentiate normal ears and otosclerotic ears pre and postsurgery, under both ambient pressure and pressurized conditions.
Keywords: middle ear; acoustic impedance tests; otosclerosis